Human Resources Planning Using Workload and Job Analysis as the Basis of Improving the Organizational Structure in the Marketing (Case Study of Pt. IMST) - Ni Gusti Made Rai; Amanullah Baihaqi; Prahardika Prihananto; Syarifa Hanoum (Jurnal Sosial Humaniora, 2023)
Strategic planning is crucial for every company to achieve organizationalgoals, with a focus on effectiveness, efficiency, and productivity in humanresource management. Human resource planning involves analyzingworkloads in alignment with job descriptions for each position. This researchwas carried out within PT IMST's Marketing Division, a company operatingin the railroad component distribution and trading industry. The primaryobjective was to examine employee workloads and integrate the findings withjob analysis to inform human resource planning. The study revealed thatincreased market penetration and project demand have led to higher physicaland mental workloads for workers. The NASA TLX method was employed toconduct the workload analysis. Based on the research results, it isrecommended that the optimal number of personnel be five for each positionof Head and Junior Specialist, four for Project Achievement Staff I, three forProject Achievement Staff II, and six for Administrative Staff. To addressthese staffing needs, human resource planning should prioritize recruiting oradding personnel who possess the requisite qualifications and competencies inaccordance with the established positions. By aligning recruitment effortswith the workload analysis and job descriptions, the company can ensure thatits workforce is appropriately sized and equipped to efficiently meet marketdemands and achieve organizational success.